Confirmation of bacterial ring rot detection using realtime PCR with an internal reaction control - Smith, D; Boer, Solke H. De; Gourley, J (MTT, 2007)
The ring rot disease of potato, caused by the Gram-positive bacterium, Clavibacter michiganensis subsp. sepedonicus (Cms), is under good regulatory control in Canada. With a zero tolerance for the disease in seed potato production, and a certification requirement for annual laboratory indexing of selected seed lots for the possible presence of asymptomatic latent infections, occurrences of bacterial ring rot are infrequent and limited in scope. The laboratory indexing requirement is considered to be a particularly important component of the seed certification program for ring rot control, because the disease, when first present, is, under Canadian production conditions, often not detected by field inspection of growing crops or by bin inspection of harvested tubers, and will be of increasing importance should changing climatic conditions impact negatively on symptom expression. In Canada, the primary test for laboratory indexing is the enzyme-linked immunosorbent assay (ELISA) with a monoclonal antibody targeting the Cms extracellular polysaccharide, followed by a somatic antigen-directed monoclonal antibody-based immunofluorescence (IMF) confirmatory test for ELISA positive samples. A real-time (kinetic) PCR test (kPCR) using TaqMan chemistry, adapted from a published method and supplemented with an internal reaction control (RC) was implemented to evaluate the efficiency of the serological methods. The RC was constructed from a corn invertase gene fragment flanked by sequences complementary to the Cms primers, and was designed to generate an amplicon that differed from the Cms-specific amplicon but by its amplification would confirm the absence of PCR inhibitory substances in template DNA. The RC construct was cloned into plasmid vector pCRII-TOPO (to create plasmid, pCmsC4) and propagated in Escherichia coli strain DHá-T1. The RC amplicon did not hybridize to the Cms-specific TaqMan probe, but could be detected in kPCR runs with the inclusion of SYBR Green in the reaction mix. The Cmsspecific and the RC amplicons were readily distinguished by their respective postamplification melting temperatures in the presence of SYBR Green. The addition of 100 copies of pCmsC4 to the reaction mix did not adversely affect sensitivity of Cms detection by kPCR. The presence of Cms in all ELISA/IMF-positive samples was confirmed by kPCR. However, in a 320-sample data set, 50% of ELISA-positive samples with cell counts below the IMF threshold were positive by kPCR, verifying the applicability of kPCR as a valuable additional confirmatory test. In the same data set, 16% of samples that had both ELISA and IMF readings below the positive thresholds were positive by kPCR. While it was difficult to discount entirely the possibility of false positive kPCR tests resulting from crosscontamination during collection and processing of samples or PCR setup, the data confirms the greater sensitivity of kPCR for detecting asymptomatic (latent) infections of bacterial ring rot.
Keywords: Ka; ring rot; indexing; detection; kPCR; ELISA; immunofluorescence2